2018
DOI: 10.3389/fncel.2018.00224
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Enrichment Improves Cognitive Deficits, AD Hallmarks and Epigenetic Alterations Presented in 5xFAD Mouse Model

Abstract: Cumulative evidence shows that modifications in lifestyle factors constitute an effective strategy to modulate molecular events related to neurodegenerative diseases, confirming the relevant role of epigenetics. Accordingly, Environmental Enrichment (EE) represents an approach to ameliorate cognitive decline and neuroprotection in Alzheimer’s disease (AD). AD is characterized by specific neuropathological hallmarks, such as β-amyloid plaques and Neurofibrillary Tangles, which severely affect the areas of the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
54
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(62 citation statements)
references
References 93 publications
(118 reference statements)
7
54
1
Order By: Relevance
“…are consistent with previous studies of nine month old 5XFAD mice [35]. Furthermore, a consistent decrease in synaptophysin or PSD95 has not been observed prior to nine months of age [35,63,[74][75][76]. Future experiments with mice over nine months of age might exacerbate this difference (AD pathology due to Aβ toxicity is age-dependent), potentially leading to more robust synaptic pathology, allowing for a more effective evaluation of CAW's impact on synaptic density.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…are consistent with previous studies of nine month old 5XFAD mice [35]. Furthermore, a consistent decrease in synaptophysin or PSD95 has not been observed prior to nine months of age [35,63,[74][75][76]. Future experiments with mice over nine months of age might exacerbate this difference (AD pathology due to Aβ toxicity is age-dependent), potentially leading to more robust synaptic pathology, allowing for a more effective evaluation of CAW's impact on synaptic density.…”
Section: Discussionsupporting
confidence: 89%
“…We found a statistically significant CAW treatment-dependent increase in these synaptic markers in the cortex, while there was a significant increase in synaptophysin in the hippocampus and an increasing trend in Psd95 (p=0.026) with CAW treatment. An interesting observation in the progression of 5XFAD pathology is that spine loss (4-9 months) [62] occurs subsequent to cognitive dysfunction (3-6 months) [35,[63][64][65][66] and Aβ plaque formation (two months) [67]. This is different from the progression in Tg2576, which manifests synaptic damage at an early stage of pathological development (4.5 months) [68,69] with a corresponding decrease in synaptic density markers [70] prior to Aβ plaque development (10 months) [71] and cognitive deficiencies (one year) [72,73].…”
Section: Discussionmentioning
confidence: 99%
“…3). Decrease in synaptophysin level in 5XFAD mice was not clearly detected at least by western blotting as other reports showing 23,24 . More fine detection of synaptophysin at limited presynaptic areas might be needed in future.…”
Section: Discussioncontrasting
confidence: 52%
“…Both SNY and PSD95 play an essential role in synaptic plasticity [39]. With this respect, several studies have demonstrated that the protein expressions of SYN and PSD95 in the AD's hippocampus were enhanced signi cantly, and decreases in these protein expressions can restrain cognitive decline [40,41]. In this study, using Golgi-Cox staining, we found that the dendritic spines in hippocampal CA3 and DG subsets in APP/PS1 mice were markedly reduced, and the protein levels of SYN and PSD95 in the hippocampus were decreased as well.…”
Section: Discussionmentioning
confidence: 99%